Inseminação artificial em tempo fixo intracornual profunda em bovinos - Fidelis, Cicero Antonio Sobreira (2020)
Currently, through Artificial Fixed-Time Insemination (IATF), it is possible to achieve pregnancy rates in beef cattle, nulliparous, primiparous and multiparous, respectively 49.1%, 47.4% and 54.0%. In this context, the search for improvements in the efficiency of available artificial insemination (AI) technique is still required. Therefore, the objective of this study was to compare design rates in inseminated cows by artificial insemination in fixed-time intracornual (IATF-IC) and artificial insemination in fixed-time transcervical (IATF-TC). The experiment was carried out in the rural area of the municipality of Conceição do Araguaia-PA with 68 cows, submitted to the following protocol; D0 at 08:00 h, received an intravaginal P4 release device associated with 2.0mg estradiol benzoate intramuscularly (im). D8 at 8:00 p.m., the P4 device was withdrawn and administered 12.5 mg of Dinoprost tromethamine (im); 1.0mg Estradiol Cypionate (im) and 300UI Equine Chorionic Gonadotrophin (im). D10 at 08:00 h, 34 cows were inseminated in the uterine body and 34 inseminated intracornual, ipsilateral to the ovary with preovulatory follicle. After 45 days, the diagnosis of gestation was performed by transrectal ultrasonography. The conception rate found with semen deposition in the uterine body was 32%, while deep intracornual deposition was 26%. The results demonstrated a non-significant difference between the techniques (p> 0.05). The results of this study suggest that the intracornual technique does not allow its use. However, more studies need to be done to standardize the technique and scientific validation, considering its perspectives of use.